1998
DOI: 10.1016/s0014-5793(98)01219-8
|View full text |Cite
|
Sign up to set email alerts
|

Developmentally and wound‐regulated expression of the gene encoding a cell wall copper amine oxidase in chickpea seedlings1

Abstract: A chickpea cDNA encoding a cell wall copper amine oxidase (CuAO) was cloned and characterised. The 2010 bp open reading frame encodes a protein of 76.5 kDa which shares significant primary structure homology with other known CuAOs. Southern blot analysis indicates that in chickpea CuAO is encoded by a single gene or a small gene family. This cDNA was essential for studying the role of CuAO during seedling development and wound healing in chickpea seedlings. CuAO transcript level and activity were modulated dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
54
0
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 23 publications
2
54
0
2
Order By: Relevance
“…Participation of these enzymes in the lignification process is quite obvious from many studies on the influence of biotic or abiotic stress factors on plants, e.g. wounding, attack of pathogen (Angelini et al 1993, Rea et al 1998. The markedly higher amine oxidase activity of etiolated pea correlates with faster growth requiring e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participation of these enzymes in the lignification process is quite obvious from many studies on the influence of biotic or abiotic stress factors on plants, e.g. wounding, attack of pathogen (Angelini et al 1993, Rea et al 1998. The markedly higher amine oxidase activity of etiolated pea correlates with faster growth requiring e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Immunolocalization studies demonstrated the presence of amine oxidase in cortical cell walls and in xylem tissue (Angelini et al 1990). It was suggested that H 2 O 2 , generated by amine oxidation, was important for lignification both in normal and stress conditions (Angelini et al 1993, Rea et al 1998.…”
mentioning
confidence: 99%
“…Despite extensive research on the source of ROS, the subcellular location and the mechanism of ROS generation has not been unequivocally clarified (Bolwell, 1999). Many different mechanisms have been shown to be involved in pathogeninduced ROS production, including peroxidases and diverse oxidases (oxalate oxidase, amine oxidase, and NADPH oxidase; Pugin et al, 1997;Wojtaszek, 1997;Rea et al, 1998). An intracellular and an apoplastic source of ROS production were detected during elicitation of tobacco (Nicotiana tabacum) epidermal cells with cryptogein from Phytophthora cryptogea (Allan and Fluhr, 1997).…”
mentioning
confidence: 99%
“…In this context, proteins involved in the regulation of H 2 O 2 levels in the extracellular matrix probably play a crucial role. In the apoplast, the accumulation of H 2 O 2 may result by the activity of a plasma membrane NAD(P)H oxidases (Doke, 1995; Lamb and Dixon, 1997), cell wall oxalate oxidases (Lane, 1994), peroxidases (Bolwell et al, 1995), and FAD and copper-containing amine oxidase (Allan and Fluhr, 1997;Rea et al, 1998; Laurenzi et al, 1999).Copper amine oxidase (CuAO; EC 1.4.3.6) catalyzes the oxidative deamination of various biological active amines with the production of the corresponding aminoaldehydes, H 2 O 2 , and NH 3 (Smith, 1985). The production of H 2 O 2 raised upon amine degradation has been correlated with oxidative burst, cell death, as well as peroxidase-mediated lignification, suberization, and cell wall polymer cross-linking occurring during ontogenesis and defense responses (Allan and Fluhr, 1997; Møller and McPherson, 1998;Rea et al, 1998;Wisniewski et al, 2000 Article, publication date, and citation information can be found at www.plantphysiol.org/cgi…”
mentioning
confidence: 99%
“…In this context, proteins involved in the regulation of H 2 O 2 levels in the extracellular matrix probably play a crucial role. In the apoplast, the accumulation of H 2 O 2 may result by the activity of a plasma membrane NAD(P)H oxidases (Doke, 1995; Lamb and Dixon, 1997), cell wall oxalate oxidases (Lane, 1994), peroxidases (Bolwell et al, 1995), and FAD and copper-containing amine oxidase (Allan and Fluhr, 1997;Rea et al, 1998; Laurenzi et al, 1999).…”
mentioning
confidence: 99%